Revision of Ooctonus in the Neotropical region and comparison with Boudiennyia (Hymenoptera: Mymaridae) - Huber, John T. (Zootaxa, 2013)
Ooctonus Haliday (Hymenoptera: Mymaridae) contains four species in the Neotropical Region: O. clebschi Huber, sp. n., O. costaricensis Huber, sp. n., O. woolleyi Huber, sp. n., and O. zolnerowichi Huber, sp. n. Ooctonus costaricensis represents the furthest south Ooctonus has been recorded in the New World. An illustrated identification key to females is given. The genus is compared with Boudiennyia Girault, known only from Australia and New Caledonia. Despite many similarities, Ooctonus is treated as a somewhat isolated clade whereas Boudiennyia, apparently the most similar genus to Ooctonus, is treated as the basal clade of Mymarini sensu Annecke and Doutt. Reduction in tarsal number has occurred at least four times in three distantly related clades of extant Mymaridae: in Eoforesteria Mathot and Ptilomymar Annecke & Doutt, the latter newly placed in the Camptoptera-group of genera, in Kikiki Huber & Beardsley in the Anagrus group of genera, and in Mymarini except for Boudiennyia, and perhaps also Ooctonus.